NLR network mediates immunity to diverse plant pathogens - Wu, Chih-Hang (Proc Natl Acad Sci U S A, 2017)
Both plants and animals rely on nucleotide-binding domain and leucine-rich repeat-containing (NLR) proteins to respond to invading pathogens and activate immune responses. An emerging concept of NLR function is that “sensor” NLR proteins are paired with “helper” NLRs to mediate immune signaling. However, our fundamental knowledge of sensor/helper NLRs in plants remains limited. In this study, we discovered a complex NLR immune network in which helper NLRs in the NRC (NLR required for cell death) family are functionally redundant but display distinct specificities toward different sensor NLRs that confer immunity to oomycetes, bacteria, viruses, nematodes, and insects. The helper NLR NRC4 is required for the function of several sensor NLRs, including Rpi-blb2, Mi-1.2, and R1, whereas NRC2 and NRC3 are required for the function of the sensor NLR Prf. Interestingly, NRC2, NRC3, and NRC4 redundantly contribute to the immunity mediated by other sensor NLRs, including Rx, Bs2, R8, and Sw5. NRC family and NRC-dependent NLRs are phylogenetically related and cluster into a well-supported superclade. Using extensive phylogenetic analysis, we discovered that the NRC superclade probably emerged over 100 Mya from an NLR pair that diversified to constitute up to one-half of the NLRs of asterids. These findings reveal a complex genetic network of NLRs and point to a link between evolutionary history and the mechanism of immune signaling. We propose that this NLR network increases the robustness of immune signaling to counteract rapidly evolving plant pathogens.